2019
DOI: 10.1159/000495888
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Cancer Management: Isolated Limb Infusion for Sarcoma

Abstract: <b><i>Background:</i></b> Sarcoma is a heterogeneous group of malignancies comprising almost 80 subtypes of bone and soft tissue cancers. Previously, all subtypes were managed identically. Advancements in biological and genetic studies have revealed that sarcoma subtypes display varying characteristics and therefore require tailored treatments. Locally advanced soft tissue malignancies of both the trunk and the extremities can present significant challenges for treatment. At present, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Perhaps in looking forward, we should look to the past and reconsider the role of neoadjuvant ILI in high-risk and borderline-resectable STS. Additionally, 2 of the patients recently reported by Teras et al received ILI in the adjuvant setting following resection of disease [ 26 ]. Though outcomes specific to those patients were not reported, the use of ILI as adjuvant therapy in resected STS is worth additional consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps in looking forward, we should look to the past and reconsider the role of neoadjuvant ILI in high-risk and borderline-resectable STS. Additionally, 2 of the patients recently reported by Teras et al received ILI in the adjuvant setting following resection of disease [ 26 ]. Though outcomes specific to those patients were not reported, the use of ILI as adjuvant therapy in resected STS is worth additional consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Another single-institution series by Teras et al in 2019 reported the retrospective outcomes of 10 patients who underwent ILI with melphalan and actinomycin D for unresectable, locally advanced STS from 2014 to 2018 [ 26 ]. At 3 months, ORR was 100% with CR in 30% of patients.…”
Section: Application Of Isolated Limb Infusion In Soft Tissue Sarcoma...mentioning
confidence: 99%